Oral health-related quality of life and depression/anxiety in long-term recurrence-free patients after treatment for advanced oral squamous cell cancer - Hassel, Alexander J.; Danner, Daniel; Freier, Kolja; Hofele, Christof; Becker-Bikowski, Kirsten; Engel, Michael (Journal of cranio-maxillofacial surgery, 2012)
This report focuses on the association between oral health-related quality of life (OHRQoL) and depression/anxiety of a homogeneous group of cancer patients who were recurrence-free for 8 years after treatment for advanced oral squamous cell.